A coated welding rod and its coating and preparation method

By adjusting the component ratio and adding rare earth elements to the welding rod coating, the detailed welded metal structure is formed, which solves the shortcomings of existing welding materials in low-temperature impact performance and welding stability, and achieves high strength of the weld. High toughness and full position welding capability.

CN115781107BActive Publication Date: 2025-02-14SHANDONG JULI WELDING CO LTD +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211409183.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-11
Publication Date
2025-02-14
Estimated Expiration
2042-11-11

AI Technical Summary

Technical Problem

The existing low-alloy high-strength steel welding materials have poor performance in low-temperature impact performance and welding stability, making it difficult to meet the welding needs of high-end equipment.

Method used

A kind of drug skin welding rod is used, and its drug skin is composed of marble, fluorite, barium carbonate, titanium dioxide, ferrosilicon, manganese metal, nickel powder, iron molybdenum, rare earth fluorinated, iron powder, etc., by adjusting the component ratio and adding rare earths Elements form refined deposited metal structure, enhance weld strength and toughness, and improve the "short slag" characteristics of welding slag through titanium dioxide.

Benefits of technology

It significantly improves the low-temperature impact performance and welding stability of the welding rod. The weld has high strength and high toughness, which is suitable for full-position welding. At the same time, it reduces the content of harmful elements in the weld, reduces crack sensitivity, and improves stretching and Impact performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115781107B_ABST
    Figure CN115781107B_ABST
Patent Text Reader

Abstract

The present invention provides a coated electrode and its coating and preparation method, and specifically relates to the field of welding materials. The electrode coating of the present invention comprises the following components and the weight proportions of each component are: 20-25 parts of marble, 23-28 parts of fluorite, 6-8 parts of barium carbonate, 6-9 parts of titanium dioxide, 4-5 parts of ferrosilicon, 1-2 parts of potassium feldspar, 5-7 parts of metal manganese, 4-5 parts of nickel powder, 1-2 parts of ferromolybdenum, 1-2 parts of rare earth fluoride, 17-22 parts of iron powder, 0.5-1 part of sodium carbonate, 0.3-0.6 parts of ferroboron, 0.5-1 part of sodium carboxymethyl cellulose, and 0.2-0.5 parts of graphite. The coated electrode of the present invention has good welding in all positions, small spatter, good slag removal, beautiful weld formation, and the electrode deposited metal has high strength and toughness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of welding materials, and in particular to a coated welding rod, a coating thereof and a preparation method thereof. Background Art

[0002] In recent years, with the development of large-scale and lightweight equipment, high-strength steel has been used more and more widely. my country has successively introduced and developed a variety of low-alloy high-strength steels for use in production and manufacturing in various fields, such as marine engineering, high-pressure vessels, engineering machinery, etc. Due to the increasingly harsh operating conditions, the rapid development of domestic low-alloy high-strength steel technology has put forward higher requirements for supporting welding materials. Due to the high reliability of electrode welding, the welding of some high-end equipment such as pressure vessels is still mainly based on electrode welding. Although the manufacturing level of domestic low-alloy high-strength steel welding materials has been continuously improved, the control ability in terms of low-temperature impact performance and welding stability has not reached the advanced level. Summary of the invention

[0003] In view of the above shortcomings of the prior art, the present invention provides a coated welding rod and its coating and a preparation method to improve the problems of poor low-temperature impact performance and welding stability of the welding rod.

[0004] To achieve the above-mentioned purpose and other related purposes, the present invention provides a welding rod coating, comprising the following components and the weight proportions of each component are respectively: 20-25 parts of marble, 23-28 parts of fluorite, 6-8 parts of barium carbonate, 6-9 parts of titanium dioxide, 4-5 parts of ferrosilicon, 1-2 parts of potassium feldspar, 5-7 parts of metallic manganese, 4-5 parts of nickel powder, 1-2 parts of ferromolybdenum, 1-2 parts of rare earth fluoride, 17-22 parts of iron powder, 0.5-1 part of sodium carbonate, 0.3-0.6 part of ferroboron, 0.5-1 part of sodium carboxymethyl cellulose, and 0.2-0.5 part of graphite.

[0005] In an example of the present invention, the titanium dioxide is selected from any one or a combination of rutile and titanium dioxide.

[0006] In an example of the present invention, the rare earth fluoride includes cerium fluoride.

[0007] In an example of the present invention, the calcium carbonate content in the marble is ≥96wt%, the silicon content in the ferrosilicon is 40-45wt%, the calcium fluoride content in the fluorite is ≥95wt%, the molybdenum content in the ferromolybdenum is 50-60wt%, the boron content in the ferroboron is 19-22wt%, the manganese content in the metallic manganese is ≥99wt%, and the nickel content in the nickel powder is ≥99wt%.

[0008] In one example of the present invention, the particle size of each component in the drug coating is 40 to 80 meshes.

[0009] The invention provides a coated welding rod, comprising a coating and a welding core. The coating comprises the following components, and the weight proportions of the components are respectively: 20-25 parts of marble, 23-28 parts of fluorite, 6-8 parts of barium carbonate, 6-9 parts of titanium dioxide, 4-5 parts of ferrosilicon, 1-2 parts of potassium feldspar, 5-7 parts of metallic manganese, 4-5 parts of nickel powder, 1-2 parts of ferromolybdenum, 1-2 parts of rare earth fluoride, 17-22 parts of iron powder, 0.5-1 part of sodium carbonate, 0.3-0.6 part of ferroboron, 0.5-1 part of sodium carboxymethyl cellulose, and 0.2-0.5 part of graphite.

[0010] In an example of the present invention, the welding core is an H08E welding core, and the diameter of the welding core is 3.2-5 mm.

[0011] The invention provides a method for preparing a coated welding rod, comprising the following steps: uniformly mixing the above components to prepare a coating; adding a binder to the coating, stirring uniformly to form a coating mixture; pressing the coating mixture onto the surface of a welding core, and drying to obtain a coated welding rod.

[0012] In an example of the present invention, the adhesive is a water glass adhesive, and the mass of the adhesive is 20-25% of the total mass of the coating.

[0013] In an example of the present invention, the weight of the coating mixture in the coated welding rod after drying is 35-40% of the total weight of the coated welding rod.

[0014] The electrode coating of the present invention refines the deposited metal structure and distributes it evenly by adjusting the ratio of silicon and manganese, the content of nickel and molybdenum, and the addition of rare earth elements; metal chromium, ferrosilicon, ferromolybdenum, and nickel powder can transition alloy elements into the weld to enhance the weld strength; a CB-Ti structure is formed by adding boron, carbon, and titanium, and its dispersed crystallization nucleus elements accelerate the nucleation of needle-shaped ferrite in the molten pool, refine the grains, and enhance the toughness of the deposited metal; titanium dioxide is added to form the welding slag with "short slag" characteristics, which is beneficial to weld formation, stabilizes the arc, and improves the all-position welding processability.

[0015] The coated welding rod of the present invention adopts the coating of the present invention, has the advantages of good slag removal, beautiful weld formation, and stable welding quality; the weld has the characteristics of high strength and high toughness, and can be used for all-position welding. In addition, the coated welding rod of the present invention uses H08E as a welding core, which can reduce the content of harmful elements such as S, P, H, Q, and N in the weld metal, so that the weld metal is purer and has a uniform structure, which can reduce the crack sensitivity of the weld and improve the tensile and impact properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0017] Figure 1 The present invention is a flow chart of the preparation of the Chinese medicine coated welding rod. DETAILED DESCRIPTION

[0018] The following is an explanation of the embodiments of the present invention by specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the features in the following embodiments and the embodiments can be combined with each other without conflict. It should also be understood that the terms used in the embodiments of the present invention are intended to describe specific embodiments, rather than to limit the scope of protection of the present invention. The test methods for which specific conditions are not specified in the following examples are usually carried out under conventional conditions or according to the conditions recommended by the manufacturers.

[0019] It should be noted that "%" and "wt%" in this specification represent mass percentage, and "part" represents part by weight.

[0020] The invention provides a welding rod coating, comprising the following components and the weight proportions of the components are respectively: 20-25 parts of marble, 23-28 parts of fluorite, 6-8 parts of barium carbonate, 6-9 parts of titanium dioxide, 4-5 parts of ferrosilicon, 1-2 parts of potassium feldspar, 5-7 parts of metallic manganese, 4-5 parts of nickel powder, 1-2 parts of ferromolybdenum, 1-2 parts of rare earth fluoride, 17-22 parts of iron powder, 0.5-1 part of sodium carbonate, 0.3-0.6 part of ferroboron, 0.5-1 part of sodium carboxymethyl cellulose and 0.2-0.5 part of graphite.

[0021] The functions of the components in the coating of the coated electrode are as follows:

[0022] Marble, barium carbonate: The content of calcium carbonate in marble is ≥96wt%. The main functions of calcium carbonate and barium carbonate are slag-making and gas-making, which have the functions of adjusting the alkalinity of slag, stabilizing the arc, refining the molten droplets, and desulfurizing and dephosphorizing. The decomposition temperature of calcium carbonate is 900°C, and the decomposition temperature of barium carbonate is 1400°C. The difference in the decomposition temperature of calcium carbonate and barium carbonate can effectively prolong the existence time of the molten pool, reduce the sensitivity of pores, and prevent slag collapse and slag sticking, and has good slag removal properties. The weight proportion of marble in the coating of the present invention is 20 to 25 parts, and the weight proportion of barium carbonate is 6 to 8 parts. For example, the weight proportion of marble can be any value within the range of 20 to 25 parts, such as 20 parts, 22 parts or 25 parts, and the weight proportion of barium carbonate can be any value within the range of 6 to 8 parts, such as 6 parts, 7 parts or 8 parts.

[0023] Fluorite: The main component is calcium fluoride, which is a strong diluent and can reduce the porosity sensitivity of the weld and increase the fluidity of the welding slag. The weight percentage of fluorite in the coating of the present invention is 23 to 28 parts, for example, the weight percentage of fluorite can be any value within the range of 23 to 28 parts, such as 23 parts, 25 parts or 28 parts.

[0024] Titanium dioxide: stable arc, slag formation, good thermal slag removal, can refine transition droplets, adjust slag surface tension and fluidity, and make the weld shape beautiful. The weight proportion of titanium dioxide in the coating of the present invention is 6 to 9 parts, for example, the weight proportion of titanium dioxide can be any value within the range of 6 to 9 parts, such as 6 parts, 7 parts or 9 parts.

[0025] The main function of ferrosilicon, nickel powder and iron powder is to transfer metal elements into the weld to improve the weld strength. The weight proportion of ferrosilicon in the coating of the present invention is 4 to 5 parts, the weight proportion of nickel powder in the coating is 4 to 5 parts, and the weight proportion of iron powder in the coating is 17 to 22 parts. For example, the weight proportion of ferrosilicon can be any value within the range of 4 to 5 parts, such as 4 parts, 4.5 parts or 5 parts, the weight proportion of nickel powder can be any value within the range of 4 to 5 parts, such as 4 parts, 4.5 parts or 5 parts, and the mass fraction of iron powder can be any value within the range of 17 to 22 parts, such as 17 parts, 20 parts or 22 parts.

[0026] Metal manganese: Manganese is a good deoxidizer and desulfurizer. Manganese and silicon work together to reduce the oxygen content in the weld. It combines with sulfur to form MnS, prevents the formation of low-melting FeS, prevents thermal cracks in the weld metal, and improves the weld's ability to resist thermal cracks. Manganese and iron can form a solid solution to improve the strength and hardness of ferrite and austenite in steel. The weight percentage of metal manganese in the coating of the present invention is 5 to 7 parts. For example, the weight percentage of metal manganese can be any value within the range of 5 to 7 parts, such as 5 parts, 6 parts or 7 parts.

[0027] Ferro-molybdenum: Molybdenum element is transferred to the weld. Molybdenum can improve the hardenability, strength and ductility of steel, eliminate or reduce the temper brittleness caused by other alloy elements, and thus greatly improve the impact toughness of steel. The weight percentage of ferro-molybdenum in the coating of the present invention is 1 to 2 parts, for example, the weight percentage of ferro-molybdenum can be any value within the range of 1 to 2 parts, such as 1 part, 1.5 parts or 2 parts.

[0028] Potassium feldspar: refines the droplets, improves the droplet transition morphology, and increases the arc voltage. The weight percentage of potassium feldspar in the coating of the present invention is 1 to 2 parts, for example, the weight percentage of potassium feldspar can be any value within the range of 1 to 2 parts, such as 1 part, 1.5 parts, or 2 parts.

[0029] Rare earth fluoride: Rare earth elements have high chemical properties and can play the role of deoxidation, desulfurization and inclusion modification in steel. They can also reduce the content of trace low-melting-point metals such as Sn, Sb and other elements, reduce the segregation of impurity elements at grain boundaries, and improve the mechanical properties of materials by strengthening grain boundaries. The weight percentage of rare earth fluoride in the coating of the present invention is 1 to 2 parts, for example, the weight percentage of rare earth fluoride can be any value within the range of 1 to 2 parts, such as 1 part, 1.5 parts or 2 parts.

[0030] Ferroboron: deoxidizes, transfers boron to the weld, and increases the hardenability of the weld. The weight percentage of ferroboron in the coating of the present invention is 0.3 to 0.6 parts, for example, the weight percentage of ferroboron can be any value within the range of 0.3 to 0.6 parts, such as 0.3 parts, 0.5 parts, or 0.6 parts.

[0031] Sodium carboxymethyl cellulose and sodium carbonate: improve the viscosity of electrode powder, increase the pressure coating, and also have certain arc stabilization performance. The weight proportion of sodium carboxymethyl cellulose in the coating of the present invention is 0.5 to 1 part, for example, the weight proportion of sodium carboxymethyl cellulose can be any value within the range of 0.5 to 1 part, such as 0.5 part, 0.7 part or 1 part; the weight proportion of sodium carbonate is 0.5 to 1 part, for example, the weight proportion of sodium carbonate can be any value within the range of 0.5 to 1 part, such as 0.5 part, 0.7 part or 1 part.

[0032] Graphite: Transition carbon element into the weld, forming CB-Ti structure with boron and titanium elements, and its dispersed crystallization nucleus element accelerates the nucleation of needle-shaped ferrite in the molten pool, refines the grains, and enhances the toughness of the deposited metal. The weight percentage of graphite in the coating of the present invention is 0.2 to 0.5 parts, for example, the graphite can be any value within the range of 0.2 to 0.5 parts, such as 0.2 parts, 0.4 parts or 0.5 parts.

[0033] In one embodiment, the titanium dioxide is any one or more of rutile or titanium dioxide.

[0034] In one embodiment, the rare earth fluoride includes cerium fluoride.

[0035] In one embodiment, the calcium carbonate content in the marble is ≥96wt%, the silicon content in the ferrosilicon is 40-45wt%, the calcium fluoride content in the fluorite is ≥95wt%, the molybdenum content in the ferromolybdenum is 50-60wt%, the boron content in the ferroboron is 19-22wt%, the manganese content in the metallic manganese is ≥99wt%, and the nickel content in the nickel powder is ≥99%.

[0036] In one embodiment, the particle size of the drug powder in the drug coating is 40-80 meshes, for example, the particle size of the drug powder can be any value within the range of 40-80 meshes, such as 40 meshes, 60 meshes or 80 meshes.

[0037] The coated welding rod of the present invention comprises a coating and a welding core, wherein the coating comprises the following components in parts by weight: 20-25 parts of marble, 23-28 parts of fluorite, 6-8 parts of barium carbonate, 6-9 parts of titanium dioxide, 4-5 parts of ferrosilicon, 1-2 parts of potassium feldspar, 5-7 parts of metallic manganese, 4-5 parts of nickel powder, 1-2 parts of ferromolybdenum, 1-2 parts of rare earth fluoride, 17-22 parts of iron powder, 0.5-1 part of sodium carbonate, 0.3-0.6 part of ferroboron, 0.5-1 part of sodium carboxymethyl cellulose and 0.2-0.5 part of graphite.

[0038] In one embodiment, the welding core is an H08E welding core, the diameter of the welding core is 3.2-5.0 mm, the carbon content of the welding core is ≤0.1wt%, the manganese content is 0.3-0.6wt%, the silicon content is ≤0.03wt%, the sulfur content is ≤0.02wt%, the phosphorus content is ≤0.02wt%, the oxygen content is ≤0.008wt%, and the nitrogen content is ≤0.008wt%.

[0039] See also Figure 1 The present invention provides a method for preparing a coated welding rod, comprising the following steps:

[0040] S1. Mix the above components evenly to prepare a coating;

[0041] S2, adding a binder to the coating, and stirring evenly to form a coating mixture;

[0042] S3, press-coat the coating mixture on the surface of the welding core, dry it, and obtain the coating welding rod.

[0043] In step S1, the particle size of each component in the drug coating is 40 to 80 meshes. For example, the particle size of each component in the drug coating can be any value within the range of 40 to 80 meshes, such as 40 meshes, 60 meshes, or 80 meshes.

[0044] In step S2, the binder is a water glass binder, the mass of the binder is 20-25% of the total mass of the coating, and the weight of the coating mixture in the coated welding rod after drying is 35-40% of the total weight of the coated welding rod.

[0045] In step S3, the welding core is selected as H08E welding core, and the diameter of the welding core is 3.2-5 mm, for example, the diameter of the welding core can be any value within the range of 3.2-5 mm, such as 3.2 mm, 4 mm, 4.5 mm or 5 mm. The H08E welding core has less content of other harmful impurities such as sulfur and phosphorus, which can reduce the content of harmful elements such as S, P, H, Q, N in the weld metal, so that the weld metal is purer and the crack sensitivity of the weld can be reduced. The drying temperature during drying is preferably 350°C.

[0046] The present invention is described in detail below through some specific examples. The drugs used in the following examples can all be obtained through common commercial means.

[0047] Example 1

[0048] The coated welding rod of the present embodiment includes a coating and a welding core, wherein the coating includes the following components in parts by weight: 20 parts of marble, 28 parts of fluorite, 8 parts of barium carbonate, 9 parts of titanium dioxide, 4 parts of ferrosilicon, 1 part of potassium feldspar, 5 parts of metallic manganese, 5 parts of nickel powder, 2 parts of ferromolybdenum, 1 part of rare earth fluoride, 17 parts of iron powder, 0.5 parts of sodium carbonate, 0.3 parts of ferroboron, 1 part of sodium carboxymethyl cellulose, and 0.2 parts of graphite. The welding core is a 3.2mm H08E welding core. A water glass binder accounting for 20% of the total mass of the dry powder mixture is added to the above-mentioned coating, and the mixture is stirred and mixed to form a coating mixture. The coating mixture is pressed and coated on the surface of the welding core, and dried at 350°C to obtain a coated welding rod. The mass of the coating mixture after drying accounts for 35% of the total mass of the coated welding rod.

[0049] Example 2

[0050] The coated electrode of this embodiment includes a coating and a welding core, wherein the coating includes the following components in parts by weight: 25 parts of marble, 23 parts of fluorite, 6 parts of barium carbonate, 6 parts of titanium dioxide, 5 parts of ferrosilicon, 2 parts of potassium feldspar, 7 parts of metal manganese, 4.5 parts of nickel powder, 1 part of ferromolybdenum, 2 parts of rare earth fluoride, 22 parts of iron powder, 1 part of sodium carbonate, 0.6 parts of ferroboron, 0.5 parts of sodium carboxymethyl cellulose, and 0.5 parts of graphite. The welding core uses a 4.0mm H08E welding core, and a water glass binder of 25% of the total mass of the dry powder mixture is added to the above-mentioned coating, and the mixture is stirred and mixed to form a coating mixture. The coating mixture is pressed and coated on the surface of the welding core, and dried at 350°C to obtain a coated welding rod, and the mass of the coating mixture after drying accounts for 40% of the total mass of the coated welding rod.

[0051] Example 3

[0052] The coated electrode of this embodiment includes a coating and a welding core, wherein the coating includes the following components in parts by weight: 23 parts of marble, 27 parts of fluorite, 7 parts of barium carbonate, 8 parts of titanium dioxide, 4.5 parts of ferrosilicon, 2 parts of potassium feldspar, 6 parts of metal manganese, 4 parts of nickel powder, 1.5 parts of ferromolybdenum, 1.3 parts of rare earth fluoride, 20 parts of iron powder, 0.8 parts of sodium carbonate, 0.4 parts of ferroboron, 0.7 parts of sodium carboxymethyl cellulose, and 0.3 parts of graphite. The welding core uses a 5.0 mm H08E welding core, and a water glass binder of 22% of the total mass of the dry powder mixture is added to the above-mentioned coating, and the mixture is stirred and mixed to form a coating mixture, and the coating mixture is pressed and coated on the surface of the welding core, and dried at 350° C. to obtain a coated welding rod, and the mass of the coating mixture after drying accounts for 38% of the total mass of the coated welding rod.

[0053] According to relevant standards and specifications, various welding tests were carried out on the welding rods provided in the above-mentioned embodiments 1, 2 and 3. The welding process performance is shown in Table 1, the mechanical properties of the deposited metal are shown in Table 2, and the chemical composition of the deposited metal is shown in Table 3:

[0054] Table 1 Welding process performance

[0055]

[0056] Table 2 Deposited metal properties

[0057]

[0058] Table 3 Chemical composition of deposited metal

[0059]

[0060] The test results of Examples 1 to 3 show that the coated welding rod provided by the present invention has good welding performance in all positions, small spatter, good slag removal performance, beautiful weld formation, and the electrode deposited metal has high strength and toughness.

[0061] The electrode coating of the present invention refines the deposited metal structure and distributes it evenly by adjusting the ratio of silicon and manganese, the content of nickel and molybdenum, and the addition of rare earth elements; metal chromium, ferrosilicon, ferromolybdenum, and nickel powder can transition alloy elements to the weld to enhance the weld strength; by adding boron, carbon, and titanium to form a CB-Ti structure, its dispersed crystallization nucleus elements accelerate the nucleation of needle-shaped ferrite in the molten pool, refine the grains, and enhance the toughness of the deposited metal; adding titanium dioxide makes the welding slag form a "short slag" characteristic, which is conducive to weld formation, stabilizes the arc, and improves the processability of all-position welding. The coated welding rod of the present invention, using the coating of the present invention, has the advantages of good slag removal, beautiful weld formation, and stable welding quality; the weld has the characteristics of high strength and high toughness, and can be used for all-position welding. In addition, the coated welding rod of the present invention uses H08E as a welding core, which can reduce the content of harmful elements such as S, P, H, Q, and N in the weld metal, so that the weld metal is purer and uniform in structure, which can reduce the crack sensitivity of the weld and improve the tensile and impact properties. Therefore, the present invention effectively overcomes some practical problems in the prior art and thus has high utilization value and use significance.

[0062] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A welding rod coating, characterized in that: The electrode coating is composed of the following components, and the weight proportions of each component are respectively: 20-25 parts of marble, 23-28 parts of fluorite, 6-8 parts of barium carbonate, 6-9 parts of titanium dioxide, 4-5 parts of ferrosilicon, 1-2 parts of potassium feldspar, 5-7 parts of metallic manganese, 4-5 parts of nickel powder, 1-2 parts of ferromolybdenum, 1-2 parts of rare earth fluoride, 17-22 parts of iron powder, 0.5-1 part of sodium carbonate, 0.3-0.6 parts of ferroboron, 0.5-1 part of sodium carboxymethyl cellulose, and 0.2-0.5 part of graphite, wherein the titanium dioxide is selected from any one or a combination of two of rutile and titanium dioxide, the rare earth fluoride includes cerium fluoride, the calcium carbonate content in the marble is ≥96 wt%, the silicon content in the ferrosilicon is 40-45 wt%, the calcium fluoride content in the fluorite is ≥95 wt%, and the molybdenum content in the ferromolybdenum is 50-60 wt%. wt%, the content percentage of boron element in the ferroboron is 19-22 wt%, the manganese content in the metallic manganese is ≥99 wt%, and the nickel content in the nickel powder is ≥99 wt%.

2. The electrode coating according to claim 1, characterized in that: The particle size of each component in the medicine coating is 40-80 meshes.

3. A coated welding rod, characterized in that: The invention comprises a coating and a welding core, wherein the coating is composed of the following components, and the weight proportions of the components are respectively: 20-25 parts of marble, 23-28 parts of fluorite, 6-8 parts of barium carbonate, 6-9 parts of titanium dioxide, 4-5 parts of ferrosilicon, 1-2 parts of potassium feldspar, 5-7 parts of metallic manganese, 4-5 parts of nickel powder, 1-2 parts of ferromolybdenum, 1-2 parts of rare earth fluoride, 17-22 parts of iron powder, 0.5-1 part of sodium carbonate, 0.3-0.6 parts of ferroboron, 0.5-1 part of sodium carboxymethyl cellulose and 0.2-0.5 part of graphite.

4. The coated welding electrode according to claim 3, characterized in that: The welding core is a H08E welding core, and the diameter of the welding core is 3.2~5.0mm.

5. A method for preparing a coated welding electrode, characterized in that: The steps include: The components according to claim 1 are mixed uniformly to prepare a coating; Adding a binder to the coating and stirring evenly to form a coating mixture; The coating mixture is pressed onto the surface of the welding core and dried to obtain the coating welding rod.

6. The preparation method according to claim 5, characterized in that: The adhesive is a water glass adhesive, and the mass of the adhesive is 20-25% of the total mass of the coating.

7. The preparation method according to claim 5, characterized in that: The weight of the coating mixture in the coated welding rod after drying is 35-40% of the total weight of the coated welding rod.

Citation Information

Patent Citations

  • Ultralow-hydrogen low-alloy steel electrode for low-temperature steel

    CN104128717A

  • High-strength steel welding rod for hydroelectric engineering and preparation method for high-strength steel welding rod

    CN107931888A